Multinational enterprises and global value chains: the OECD analytical AMNE database - Cadestin, Charles (OECD Publishing, 2018)
In order to better understand the interdependencies between trade and investment in global value chains (GVCs), the OECD has developed a new dataset on the Activities of Multinational Enterprises (AMNE). This dataset starts from official AMNE statistics and combines the information with Inter-Country Input-Output (ICIO) tables to provide new insights on the trade-investment nexus in GVCs. This dataset allows the contribution of domestic firms, multinational enterprises (MNEs) and their foreign affiliates to global trade and production to be assessed. This paper details the methodology that was used to create the data, as well as the main assumptions and challenges in the work
Keywords: Trade